Scarf osteotomy without internal fixation for correction of hallux valgus: A clinical and radiographic review of 148 cases. Issue 3 (June 2018) - Curtin, M.; Murphy, E.; Bryan, C.; Moroney, P.
Highlights: Scarf steotomy without screws for fixation. Technique as described by Maestro et al. (2012, 2016) [5, 24]. 148 Cases, minimum follow-up one year. Significant improvements in radiographic and clinical function. Only 2 cases with loss of correction. Abstract: Background: Hallux valgus is a common condition with in excess of 120 procedures described in the literature for its correction. Traditionally, distal metatarsal osteotomies have been employed in the treatment of mild deformities, with proximal osteotomies being reserved for more severe presentations. The Scarf osteotomy without internal fixation allows large translations which can successfully correct severe hallux valgus deformities, without limitations related to screw placement. Methods: This is a retrospective single surgeon case series performed over a three year period. One hundred and forty-eight cases were identified, with an average follow up time of 16.5 months. Visual analogue scales were used to obtain preoperative and postoperative pain and cosmetic scores, with the Foot and Ankle Disability Index (FADI) index used to assess functional status. The hallux valgus angle (HVA) and intermetatarsal angle (IMA) were assessed on preoperative and postoperative AP weight-bearing foot X-rays. Results: The mean pain score improved from 7.04/10 preoperatively to 0.29/10 postoperatively. The mean cosmetic score improved from 2.1/10 to 9.1/10 postoperatively. The mean preoperative HVA and IMA were 35.04° and 15.04°, respectively. The mean postoperative HVA and IMA were 11.54° and 4.83°, respectively. The mean postoperative FADI score was 103.4/104. We report a loss of correction in two cases. One revision surgery was performed. Conclusions: We report a large series of cases of the modified Scarf osteotomy as described by Maestro—a versatile, cost-effective, safe and reliable technique with the potential for three dimensional correction. Whilst this is a technically demanding procedure, we recommend the use of the modified Scarf osteotomy in the treatment of a wide range of hallux valgus deformities.